KONSUMSI MINUMAN NUTRAFOSIN BERISI INULIN DAN FRUKTOOLIGOSAKARIDA (FOS) MENURUNKAN KADAR TRIGLISERIDA PENDERITA DISLIPIDEMIA - Tejasari Tejasari (JURNAL AGROTEKNOLOGI, 2011)
Food contains nutrients, including carbohydrate which has major role in energy production needed for internal and external activities. Several kinds of carbohydrate, such as inulin (fruktan) and fructooligosacharides (FOS) were proven be able to modify physiologic and biochemical process, specifically fatty acids and cholesterol metabolism. These fact showed that this both carbohydrate compounds biologically active in influencing blood lipid profile, including tryasilglycerol (TAG) or tryglycerides. Both compounds have been claimed as functional food ingredients. Health effect of inulin and FOS will be emerged if the subject has enough energy and nutrient intake. In Indonesia, clinical trial of health effect of functional food ingredient on human is difficult to be done because of problem in controlling entirely the subject food consumption. This study was done on dyslipidemic subject that fulfill inclusion requirement and willing (informed consent) to follow all experiment procedures for 21 days, with their daily food consumption pattern as usual. Dyslipidemic subjects are out patient in Subandi Hospital in Jember. Therefore, they have been given nutrition consultation from specialized medical doctor in cardiovascular diseases and from nutrition unit as well. This experiment aims to evaluate the effect of inulin and FOS intake from Nutrafosin beverage consumption on tryglycerides level of dyslipidemic whom their consumption pattern was as usual. Food consumption data was gained through 24 hours Recall Method for 3 days. Energy requirement was determined based on relative body weight (RBW). This experimental study was a clinical trial as a pararel matched pairs design. The intended sample were choosen from accesible population thru non-probability and consecutive sampling. One cup of Nutrafosin beverage contained 2 g inulin powder and 50 ml FOS that given by single blinding placebo designed to 16 dislipidemic subject for 21 days consumption orally. Tryglycerides level measurement was done at 0 days and 22th days. The tryglycerides level difference between before and after treatment from placebo and treatment groups was analyzed using statistical T-test pair at 95 % confidence interval. The result showed that Nutrafosin beverage consumption by dyslipidemic for 21 days decreased trygycerides by 18.5 percent, significantly (Tc= 1,108 < Ttab = 2,365).Kata kunci : inulin, fructooligosacharide (FOS), tryglycerides, dysl ipidemic, dietary fibreconsumption pattern